Proses Sosialisasi Anak: Tinjauan terhadap Dinamika Sosialisasi di Lingkungan Keluarga, Sekolah, dan Masyarakat dalam Konteks Pendidikan - Ma'sum, Toha; Ristianah, Niken (Kartika: Jurnal Studi Keislaman, 2023)
The process of socialization is a learning process, namely a process of accommodation in which individuals/children hold back, change impulses within themselves and adopt the way of life or culture of their society. The socialization process is also an individual learning process in behaving in accordance with the standard norms and values ​​in a society. In this learning process, an individual/child learns about behavior, habits, and other cultural patterns. Individuals / children also learn about social skills (social skills). In the process of socialization (learning) individuals/children can take place in the educational environment including the family environment, school environment, and community environment. Where the three environments have an important role and can be a manifestation of the child's learning process